2000
DOI: 10.1108/00197850010320635
|View full text |Cite
|
Sign up to set email alerts
|

Building a stronger organization through leadership development at Parke‐Davis Research

Abstract: This article describes a systematic process initiated by Parke‐Davis Pharmaceutical Research and Development to increase the leadership capabilities of its scientific management staff. Our approach to helping scientists step up to the challenging responsibility of leading others was built around four powerful ideas: imagination, leadership, application, and community. A process of university based executive education programs and follow‐up sessions was initiated to help managers shift their perspective from fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Managers play a dual role in the innovation processes: firstly, through their powers they directly affect the course of innovation processes, secondly, they must be a leader, facilitator, animator, coach, mentor or trainer, and their task is to: coordinate, diagnose and bring out human potential, moderate, stimulate, create, initiate, and to motivate. Management may rely on developing specific innovation competencies manifested as resource allocation, the choice of technology, operations management and employee development, where the competencies are ultimately determined by the over-arching influence of the firm's knowledge structure, though directly under the influence of management who work within the influence of the knowledge structure (Siguaw, Simpson, & Enz, 2006;Mumford, Scott, Gaddis, & Strange, 2002;Jones, Simonetti, & Vielhaber-Hermon, 2000;Gliddon, 2006;Szczepańska-Woszczyna & Dacko-Pikiewicz, Managerial competencies and innovations in the www.ccsenet.org/ijms International Journal of Marketing Studies Vol. 8, No.…”
Section: Discussionmentioning
confidence: 99%
“…Managers play a dual role in the innovation processes: firstly, through their powers they directly affect the course of innovation processes, secondly, they must be a leader, facilitator, animator, coach, mentor or trainer, and their task is to: coordinate, diagnose and bring out human potential, moderate, stimulate, create, initiate, and to motivate. Management may rely on developing specific innovation competencies manifested as resource allocation, the choice of technology, operations management and employee development, where the competencies are ultimately determined by the over-arching influence of the firm's knowledge structure, though directly under the influence of management who work within the influence of the knowledge structure (Siguaw, Simpson, & Enz, 2006;Mumford, Scott, Gaddis, & Strange, 2002;Jones, Simonetti, & Vielhaber-Hermon, 2000;Gliddon, 2006;Szczepańska-Woszczyna & Dacko-Pikiewicz, Managerial competencies and innovations in the www.ccsenet.org/ijms International Journal of Marketing Studies Vol. 8, No.…”
Section: Discussionmentioning
confidence: 99%
“…Leadership educators may want to consider pedagogies that explore the use of critical reflection through assignments like journaling and role play. Many scholars have suggested that these activities engage and mobilize students to act on new ideas and challenge their conventional thinking in both theory and practice (Jones, Simonetti, & Vielhaber-Hermon, 2000;Reynolds, 1999). In addition, further analysis of experiential learning technique s, and how they are applied in leadership education, as well as other academic disciplines, may be important to determining how the "Actions a Leader Must Take to Lead Critically" can be used as an interdisciplinary tool for improving students' critical thinking skills in theory and practice.…”
Section: Discussionmentioning
confidence: 99%
“…Stedman (2009) argued that leadership classrooms should seek to develop the cognitive capabilities of students by enhancing critical thinking skills. In the same way, other scholars have alluded to practicing critical reflection, a behavior that integrates personal experiences with new learning and understanding to engage and mobilize students to act on new ideas and to challenge conventional thinking in both theory and practice (Jones, Simonetti, & Vielhaber-Hermon, 2000;Reynolds, 1999). In leadership education, deep reflective learning requires students to consider the underlying dynamics of power and to question basic assumptions and practices.…”
Section: Critical Thinking Pedagogy In Leadership Studiesmentioning
confidence: 99%
“…Scholars have alluded to practicing critical reflection-a behavior that integrates personal experiences with new learning and understanding-to engage and mobilize learners to act on new ideas and to challenge conventional thinking in both theory and practice (Jones, Simonetti, & Vielhaber-Hermon, 2000;Reynolds, 1999). Scholars have alluded to practicing critical reflection-a behavior that integrates personal experiences with new learning and understanding-to engage and mobilize learners to act on new ideas and to challenge conventional thinking in both theory and practice (Jones, Simonetti, & Vielhaber-Hermon, 2000;Reynolds, 1999).…”
Section: Strategies For Developing Critical Thinking Skills and Dispomentioning
confidence: 99%
“…Critical Reflection. Scholars have alluded to practicing critical reflection-a behavior that integrates personal experiences with new learning and understanding-to engage and mobilize learners to act on new ideas and to challenge conventional thinking in both theory and practice (Jones, Simonetti, & Vielhaber-Hermon, 2000;Reynolds, 1999). By creating opportunities to practice critical leadership, instructors can encourage and facilitate the important connection between critical thinking and leadership development (see also Guthrie & King, 2004;Stedman, 2009).…”
Section: Strategies For Developing Critical Thinking Skills and Dispomentioning
confidence: 99%